Süryani ilahiyatçı İbnü’l-İbrî’nin (Bar Hebraeus) eserlerinde İslam ve müslümanlar - Dilek, Abdullah (My University, 2023)
Antakya ve Tüm Doğu Süryani Ortodoks Patrikliği bünyesinde yer alan Doğu Mafiryânlığı görevini üstlenenen teolog ve tarihçi İbnü’l-İbrî’nin (Bar Hebraeus, ö. 1286) eserleri, 13. yüzyıldan günümüze kadar araştırmacıların dikkatini çekmiştir. Süryani literatürünün son ve en parlak ismi olarak kabul edilen İbnü’l-İbrî ilahiyat, hukuk, felsefe, edebiyat, bilim ve tıp alanlarında eser kaleme almıştır. Ansiklopedist bir bilge olarak, ilmî ve edebî türlerde olağanüstü çalışmalara sahip, idarecilik vasfı olan bir din adamıdır. Kendisi Süryani edebiyatında görülen Süryani Rönesansı’nın önde gelen temsilcisidir. İbnü’l-İbrî dinî ve tarihî konuları ele alan eserlerinde İslam ve müslümanlar hakkında da açıklamalarda bulunmuştur. Bu çalışmada İbnü’l-İbrî’nin İslam ve müslüman algısı incelenmiştir.

The works of theologian and historian Bar ‘Ebroyô (Ibn al-‘Ibrî / Bar Hebraeus), who undertook the task of the Maphrianate of the East affiliated to the Syriac Orthodox Patriarchate of Antioch and All the East, attracted the attention of researchers from the 13th century to the present day. Considered as the last and most brilliant name of Syriac literature, Bar ‘Ebroyô wrote works in the fields of theology, law, philosophy, literature, science and medicine. In addition, as an encyclopedist polymath, he is a religious man who has prodigious outputs in scientific and literary genres with an administrative aspect. Also he is foremost representative of Syriac Renaisance that emerged in Syriac literature. Bar ‘Ebroyô also made explanations about Islam and muslims in his works dealing with religious and historical issues. In this study, the perception of Islam and muslims from the eyes of Bar ‘Ebroyô was examined.
Islam and muslims in the works of Syriac theologian bar „Ebroyô (Ibn al-„Ibrî / bar hebraeus)
Keywords: 13. Yüzyıl; 13th Century; Bar ‘Ebroyô; Bar Hebraeus; Bar Hebraeus, 1226-1286; Hz. Muhammed; Ibn al-‘Ibrî; Islam; İbnü’l-İbrî; İslam; Jacobites; Kur’ân; Muslims; Müslümanlar; Prophet Muhammad; Qur’ân; Süryani Edebiyatı; Süryani Rönesansı; Syriac Literature; Syriac Renaissance; Yakubiler Bar ‘Ebroyô